IMPROVEMENT OF THE MANUFACTURING TECHNOLOGY OF FIBROUS COMPOSITE MATERIALS - SMACHYLO, OKSANA; LIASHOK, IRINA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The work is devoted to the improvement of the manufacturing technology of fibrous composite materials. Modern industry requires the production of new polymer and composite materials with a high level of operational characteristics. A promising direction for the creation of such materials is the use of various methods of modification of known materials. A very important problem that determines the technical and economic efficiency of the use of new composite materials is the prediction of operational properties and the modeling of polymers related to this problem. Research in this direction was focused on the technology of obtaining PMK based on polytetrafluoroethylene with a carbon filler. Research is focused on the technology of manufacturing polymer composite material based on polytetrafluoroethylene and carbon fiber. The first stage of improving the production technology of a fibrous composite material based on polytetrafluoroethylene is the preparation of the matrix by modifying the polymer, the second stage is the modification of the surface of the fibrous filler. The work optimizes the technology of forming (pressing) the composition into the product, which helps to achieve positive results in terms of reducing moisture absorption. By improving the manufacturing technology of fibrous composite materials by modifying the polymer, modifying the surface of the fibrous filler and optimizing the technology of forming (pressing) the composition, it is possible to increase the parameters of the deformation-strength characteristics of the composite while maintaining high tribotechnical indicators; increase the strength of the PTFE composite and its wear resistance; reduce moisture absorption, increase indicators of operational properties. The further development of the production of polytetrafluoroethylene-based polymers should be based on the scientific principles of technology of polymers and composites based on them, applied materials science and physico-chemical mechanics of composite structures. Materials with a leading future for use in friction units of industrial equipment are carbon plastics based on polytetrafluoroethylene and modified fillers, which are successfully used to replace traditional materials of purpose.